The An Autoethnographic Narrative of Institutional Resilience: Ma’had Aly Nurul Qodim within the National Education System - Imro Atus Soliha; Abdul Haris; Ulil Hidayah; Benny Prasetiya; Sohirin Mohammad Solihin (International Journal of Educational Narratives, 2026)
Background. This study examines the institutional resilience of Ma’had Aly Nurul Qodim as a form of pesantren-based higher education amid inconsistencies within Indonesia’s national education system. Despite receiving formal legal recognition, Ma’had Aly continues to face significant challenges related to administrative legitimacy, accreditation, and limited affirmative state support. Purpose. This study aims to analyze how Ma’had Aly Nurul Qodim maintains institutional resilience while navigating structural constraints within the national higher education system. Methods. This research employed a qualitative case study approach combined with autoethnographic techniques. Data were collected through semi-structured interviews with institutional leaders, lecturers, and students, supported by direct observation and document analysis. Data were analyzed using thematic qualitative procedures to identify patterns of institutional resilience and adaptation. Results. The findings reveal that Ma’had Aly Nurul Qodim sustains its institutional resilience through adaptive governance, human resource development, institutional innovation, and strategic use of technology. This resilience is influenced not only by external policy environments but also by internal cultural resources such as collective ethos, social capital, and service-oriented values. However, structural limitations remain, including restricted access to state funding and incomplete integration into the national higher education system, which may affect long-term sustainability. Conclusions. The study concludes that institutional resilience in Ma’had Aly is shaped by the interaction between internal cultural strength and external policy constraints. It contributes to the discourse on higher education resilience by offering insights into how community-based institutions negotiate structural challenges while preserving their epistemological identity.